Budgeting in Chile - Blöndal, Jón R.. (OECD Publishing, 2006)
In June 2003, the Budget Office of the Ministry of Finance of Chile requested the OECD to carry out a review of the Chilean budgeting system in a similar fashion as it does for its member countries. The OECD responded positively to this request, recognising that Chile is an established observer of the OECD Working Party of Senior Budget Officials and recognising the strong interest in the Chilean budgeting system expressed by members of the Working Party
Keywords: Governance; Chile